Modeling Digital Inclusive Finance and Corporate Green Technology Innovation Towards the Formation of Green Finance and Green Economy Through Green Monetary and Fiscal Policies in 5 Advanced Asian Countries - Nasution, Wardana; Rusiadi, Rusiadi (Formosa Journal of Science and Technology, 2024)
Facing global problems such as environmental degradation and climate change. Literature analysis shows that the green economy focuses on transformation towards low-carbon development, resource efficiency and population welfare through technology and innovation. Over the past few decades, research on green finance has increased, with many publications demonstrating the importance of green finance in supporting renewable energy projects and climate-resilient urban infrastructure. Despite progress, challenges such as the global economic contraction due to COVID-19 and increasing poverty show the need for a more integrated and sustainable approach in implementing green finance and the green economy